Socialization of the Love of Saving from an Early Age at the Tarbiyah Wata'lim Bodas Elementary Madrasah, Mangunjaya Village, Anjatan District, Indramayu Regency - Dewi Kumalasari (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
This Community Service (PKM) activity aims to instill financial literacy and a habit of saving from an early age in students at the Tarbiyah Wata'lim Bodas Elementary School (MI) in Mangunjaya Village. The background to this activity is the importance of socialization as a means of developing character and role in managing money, which is a crucial foundation for future financial stability. While saving is a vital practice, this habit needs to be socialized in a structured manner from a young age to become a permanent habit. The implementation method used was an interactive socialization focused on providing education about the concept of money, the importance of saving, and its long-term benefits, primarily targeting MI students. The results of the activity indicate that the practice of saving from a young age can form good habits in managing personal finances, increase awareness of the importance of planning for a financial future, and help children cope with emergencies or achieve long-term goals. In conclusion, this socialization of a love of saving has been proven to provide a strong foundation for individual financial stability in later life.